Efektivitas Pembelajaran Interaktif Digital dalam Meningkatkan Kemampuan Menulis Teks Eksplanasi Siswa SMP - Ilawati Ilawati; Eko Suroso (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
This study aimed to examine the effectiveness of digital interactive learning in enhancing the explanatory text writing skills of SMP students within the context of the Merdeka Curriculum. Employing a pretest-posttest control group experimental design with random assignment, the study involved 30 students divided into two groups: the experimental group (n = 15) utilized Canva for Education, Padlet, and Instagram for digital interactive learning, while the control group (n = 15) followed conventional methods. Data were collected through writing tests and analyzed using an independent t-test. Results revealed a significant difference (t = 2.971, p = 0.006), with the experimental group showing greater improvement (from 76.00 to 84.00) compared to the control group (from 71.00 to 78.00), particularly in cohesion and coherence (+1.1). Qualitative data highlighted students’ enthusiasm and reflective abilities through online peer-review. However, the small sample size and short intervention duration (4 sessions) limit the generalizability of findings. Further research with larger samples is recommended for broader application.